Automatic wealth for grads... and anyone else just starting out - Masterson, Michael (John Wiley, 2006)
Choose a great career, get your first job, and rise to the top of your field, Continuously increase your income on a fast-track basis, and get the biggest raises of your life, Profit from the real estate market—even in today's uncertain market, Start or gain equity in a business that will provide an automatic future income stream, Invest in the stock market, save money on taxes, make purchases that appreciate, reduce your credit costs, and achieve financial independence while you are still young enough to enjoy your money